AMMI biplot mode; analysis of stability and adaptability of high yielding rice (Oryza sativa L.) genotypes in rainfed lowlands of the Philippines (2014)
High genotype (G) by environment (E) interaction (GEI) complicates the task of identification of rice genotypes with high and yield in the rainfed lowland (RFL) ecosystem. This paper examined 23 rice genotypes for yield and yield stability in the RFL rice ecosystem of the Philippines. The genotypes were evaluated in 12 environments composed of 31 locations over 4 wet seasons (2007-2020), in replicated RCBD. In each evaluation, amount of rain, standing water depth , and water table depth were recorded daily and the rice plants were measured for growth characteristics and yield. AMMI analysis was used to interpret the effects of G, E & GEI, on yield and yield stability. The AMMI analysis revealed that 44.4% of the total variation in grain yield was due to E, 22.2% to G, and 33.5% to GEI effects, with the first two principal components accounting for 51.7% of GEI total sum of squares. The AMMI 2-biplot model depicted genotypes Azucena-M5R-2(3), Raeline 3 (5), PSB Rc82 (11), MAHSURI (15), and IR72 (18) as highly stable across the environments, and genotypes SPYT9-CAG05DS (14), PSB Rc10 (16), NSIC Rc138 (8), SGYT29-CAG05DS (10), PSB Rc14 (7), and IR64 (13) as the most responsive for grain yield. The AMMI-biplot analysis allowed for easy visual identification of superior genotype for each set of environment. Increased number of test environment and use of stability indices, especially when large number of entries is included could enhance the accuracy of analysis and facilitate identification of genotypes with broad or specific adaptability.
Keywords: Rice breeding; Rice -- Variety